(3MdHI GdcejJ (B((3aj GdCOH hGdfhGOQ GdeJYbdI HGdNeQjGJ(B)s - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s
(3ChdgG (B:s
((3hCTcQg TcQ ef LdG(B) (3YQGFS eYGfjg aj Mdd CdaGXg aMXi ef HOjY GdHjGf HYQhS GdCaQGM s
(3BNQgG (B:s
(3hdjS GYJbGO GdeQA eG NW cag ceG Cf MGcj GdcaQ djS HcGaQ hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde, hGdMeO ddg hMOg s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B88 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B203 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B200s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B264 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B687s
Keywords: (3GdCOHs